2013
DOI: 10.1103/physrevlett.110.066101
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Deformation Modes in Nanocrystalline Pd Films Inferred from Peak Asymmetry Evolution UsingIn SituX-Ray Diffraction

Abstract: Synchrotron-based in situ tensile testing was used to study the dominant deformation mechanisms of nanocrystalline Pd thin films on a compliant substrate. An x-ray diffraction peak profile analysis reveals an (hkl) independent deformation induced peak asymmetry. It is argued that the asymmetry is caused by a broad distribution of elastic strains among individual grains and the complexity of accommodation processes. The reversal of peak asymmetry manifests the transition from heterogeneous microplasticity to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 30 publications
3
27
0
Order By: Relevance
“…This indicates that the applied stress was accommodated by grain boundary motion in addition to the observed twinning/detwinning. The observed grain growth is in line with a recent in-situ XRD study on the deformation behavior of similar sputter-deposited ncPd thin films [28], but is in contrast to measurements performed on electron beam evaporated Pd samples where no grain growth was reported up to 4% strain [29]. However, the same authors also compared the microstructure of electron-beam evaporated and magnetron sputtered samples [30] and found significantly higher initial twin densities in electron-beam evaporated Pd films.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This indicates that the applied stress was accommodated by grain boundary motion in addition to the observed twinning/detwinning. The observed grain growth is in line with a recent in-situ XRD study on the deformation behavior of similar sputter-deposited ncPd thin films [28], but is in contrast to measurements performed on electron beam evaporated Pd samples where no grain growth was reported up to 4% strain [29]. However, the same authors also compared the microstructure of electron-beam evaporated and magnetron sputtered samples [30] and found significantly higher initial twin densities in electron-beam evaporated Pd films.…”
Section: Discussionsupporting
confidence: 89%
“…On the experimental side, Lohmiller et al showed for comparable samples that the dislocation density begins to increase in the micro plastic regime starting from 0.3–0.4% applied strain [28,45]. A dislocation density of ρ = 3.5 · 10 −3 nm −2 was reported at 0% strain and 6 · 10 −3 nm −2 at 4% strain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Ref. [50] Lohmiller et al showed sliding to occur at lower strains than dislocation glide in tensile strained nanocrystalline Pd films, while it has not been observed in strained nanocrystalline Pd films with columnar structure in Refs. [6,31].…”
Section: Discrete Stress Relaxations (Dsr)mentioning
confidence: 92%